An assessment of visitors perception of Taman Tumbina zoological and botanical park at Bintulu - Samuel, Kiyui. (2005)
The ease with which the general public is kept abreast with very basic information and knowledge of wildlife and nature through various forms of media in the modern context of science and technology threatens the relevancy of zoological parks today. Given the tremendous challenges confronting zoos societies all over the world which was felt closer at home with the controversy surrounding the intended relocation of Malaysia's National Zoo only afew years ago to some other locality, it is relevant that a proper study should be carried out in order to understand the general characteristics of zoo visitors better. Knowing the demographic profile of visitors and document their perception of zoos will help contribute to a zoo revitalized functional needs in condort with the general public and visitors perceived zoo visit benefits.